The Influence of Flooding Phenomenon to Pressure Drop on Hotleg Simulator with L/D=25 - Sindhu, Marcellinus (University of Muhammadiyah Malang, 2017)
Cooling system in nuclear reactor is much influenced by counter-current flow. When a leakage is occured, coolant in primary circuit of hotleg and hot steam from reactor will flows in counter-current condition. An experimental investigation has been performed to examine the effect of flooding phenomenon on the pressure drop. It was observed using acrylic complex pipe as hotleg simulator consisting of three parts: horizontal, bend and inclined pipe. Geometrical sizes of pipes was in scale of 1/30 of the actual hotleg geometrical size in the PWR with inner diameter=25.4 mm, the horizontal pipe length L=635 mm, and inclined pipe length was 20 mm with an angle of 50o. Pressure drop was meassured by using differential pressure sensor installed in the lower-tank (RPV simulator) dan upper-tank (SG simulator). Pressure drop was observed before, during and after flooding. Based on the observation, it was found that the change of flow pattern is followed by the change of pressure drop. The results of this study were also compared with some correlations using the dimensionless superficial velocity parameter by Wallis correlation. Wallis correlation can be written as JG*1/2 + 0,3974 JL*1/2 = 0,4832 .